Magnetic Properties of Mosaic Nanocomposites Composed of Nickel and Cobalt Nanowires - Altbir-Drullinsky, D; Escrig-Murua, J; Corona-Gonzalez, R; Castillo-Sepulveda, S (Elsevier B.V., 2016)
Mosaic nanocomposites composed of nickel and cobalt nanowires arranged in different configurations were investigated using Monte Carlo simulations and a simple model that considers single-domain structures including length corrections due to the shape anisotropy. Our results showed that for an ordered array both the coercivity and the remanence decrease linearly as a function of the concentration of nickel nanowires. Besides, we obtained that the magnetic properties of an array of a certain hard magnetic material (cobalt) will not change, unless we have more than 50% of nanowires of other soft magnetic material (nickel) in the array. In principle the second material could be other soft magnetic material, but could also be a nonmagnetic material or could even be a situation in which some of the pore arrays were not filled by electrodeposition. Therefore, our results allow us to predict the behavior of magnetic mosaic nanocomposites that are promising candidates for functional electrodes, sensors, and model catalysts. © 2016 Elsevier B.V.